Determination of Ochratoxin A and Ochratoxin B in Archived Tokaj Wines (Vintage 1959-2017) Using On-Line Solid Phase Extraction Coupled to Liquid Chromatography - Kholová, Aneta; Lhotská, Ivona; Uhrová, Adéla; Špánik, Ivan; Machyňáková, Andrea; Solich, Petr; Švec, František; Šatínský, Dalibor (Toxins, 2020)
According to the EU legislation, ochratoxin A contamination is controlled in wines. Tokaj wine is a special type of sweet wine produced from botrytized grapes infected by "noble rot" Botrytis cinerea. Although a high contamination was reported in sweet wines and noble rot grapes could be susceptible to coinfection with other fungi, including ochratoxigenic species, no screening of Tokaj wines for mycotoxin contamination has been carried out so far. Therefore, we developed an analytical method for the determination of ochratoxin A (OTA) and ochratoxin B (OTB) involving online SPE coupled to HPLC-FD using column switching to achieve the fast and sensitive control of mycotoxin contamination. The method was validated with recoveries ranging from 91.6% to 99.1% with an RSD less than 2%. The limits of quantification were 0.1 and 0.2 µg L-1 for OTA and OTB, respectively. The total analysis time of the online SPE-HPLC-FD method was a mere 6 min. This high throughput enables routine analysis. Finally, we carried out an extensive investigation of the ochratoxin contamination in 59 Slovak Tokaj wines of 1959-2017 vintage. Only a few positives were detected. The OTA content in most of the checked wines did not exceed the EU maximum tolerable limit of 2 µg L-1, indicating a good quality of winegrowing and storing.
Keywords: ochratoxin A; řízení kvality; food control; ochratoxin B; víno; Quality Control; Sensitivity and Specificity; Tokaj wine; analýza potravin; kontaminace potravin; Vitis; extrakce na pevné fázi; Wine; column switching; mycotoxin; Food Contamination; chromatografie kapalinová; Ochratoxins; Food Analysis; senzitivita a specificita; Chromatography, Liquid; ochratoxiny; online extraction; chromatography; Solid Phase Extraction